Energy security international and local issues, theoretical perspectives, and critical energy infrastructures - Gheorghe, Adrian V.; Muresan, Liviu (NATO Science for Peace and Security Series C: Environmental Security, 2011)
In terms of energy security the Black Sea region is important to Europe. Inevitably and for very good reasons, a lot of attention has been given to the existing and planned pipeline routes going around or across the Black Sea. Much less attention has been given to the development of the Black Sea energy market in its own right and to the potential advantages of coping with some current and future energy issues in a multilateral regional format rather than through individual action at national level. The present book addresses, in a comprehensive manner, the current problematic of energy security and goes beyond pipeline politics, without playing down their continued significance; it addresses some topical questions related to the sustainability and resilience of energy systems as applicable to the Black Sea region.